Review on PRNP genetics and susceptibility to chronic wasting disease of Cervidae - Katayoun Moazami-Goudarzi; Olivier Andréoletti; Jean-Luc Vilotte; Vincent Béringue (Veterinary Research, 2021)
Abstract To date, chronic wasting disease (CWD) is the most infectious form of prion disease affecting several captive, free ranging and wild cervid species. Responsible for marked population declines in North America, its geographical spread is now becoming a major concern in Europe. Polymorphisms in the prion protein gene (PRNP) are an important factor influencing the susceptibility to prions and their rate of propagation. All reported cervid PRNP genotypes are affected by CWD. However, in each species, some polymorphisms are associated with lower attack rates and slower progression of the disease. This has potential consequences in terms of genetic selection, CWD diffusion and strain evolution. CWD also presents a zoonotic risk due to prions capacity to cross species barriers. This review summarizes our current understanding of CWD control, focusing on PRNP genetic, strain diversity and capacity to infect other animal species, including humans.